Effects of Teriparatide and Vibration on Bone Mass and Bone Strength in People with Bone Loss and Spinal Cord Injury: A Randomized, Controlled Trial. (28th June 2018) - Edwards, W Brent; Simonian, Narina; Haider, Ifaz T; Anschel, Alan S; Chen, David; Gordon, Keith E; Gregory, Elaine K; Kim, Ki H; Parachuri, Ramadevi; Troy, Karen L; Schnitzer, Thomas J
ABSTRACT: Spinal cord injury (SCI) is associated with marked bone loss and an increased risk of fracture. We randomized 61 individuals with chronic SCI and low bone mass to receive either teriparatide 20 μg/d plus sham vibration 10 min/d ( n = 20), placebo plus vibration 10 min/d ( n = 20), or teriparatide 20 μg/d plus vibration 10 min/d ( n = 21). Patients were evaluated for 12 months; those who completed were given the opportunity to participate in an open‐label extension where all participants ( n = 25) received teriparatide 20 μg/d for an additional 12 months and had the optional use of vibration (10 min/d). At the end of the initial 12 months, both groups treated with teriparatide demonstrated a significant increase in areal bone mineral density (aBMD) at the spine (4.8% to 5.5%). The increase in spine aBMD was consistent with a marked response in serum markers of bone metabolism (ie, CTX, P1NP, BSAP), but no treatment effect was observed at the hip. A small but significant increase (2.2% to 4.2%) in computed tomography measurements of cortical bone at the knee was observed in all groups after 12 months; however, the magnitude of response was not different amongst treatment groups and improvements to finite element‐predicted bone strength were not observed. Teriparatide treatment after the 12‐month extension resulted in further increases to spine aBMD (total increase from baseline 7.1% to 14.4%), which was greater in patients initially randomized to teriparatide. Those initially randomized to teriparatide also demonstrated 4.4% to 6.7% improvements in hip aBMD after the 12‐month extension, while all groups displayed increases in cortical bone measurements at the knee. To summarize, teriparatide exhibited skeletal activity in individuals with chronic SCI that was not augmented by vibration stimulation. Without additional confirmatory data, the location‐specific responses to teriparatide would not be expected to provide clinical benefit in this population. © 2018 American Society for Bone and Mineral Research.